Visual literacy: the interpretation of images in English classes (Eventos Pedagógicos, 2014)
My goals in this article are to discuss the area of visual literacy and summarize the talk presented at the XVI Convention of English Teachers realized by APLIEMT - The Association of English Teachers of Mato Grosso, in 2013. In the first part of the article, I investigate three key concepts that influence the education of foreign/additional secondary languages: globalization, the roles of English and new technologies. In the second part, I discuss the area of visual literacy. Finally, I refer to some activities as examples of visual literacy. Keywords: globalization; visual literacy; English language education.